Literature Riview: Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian - Rahayu, Nita; Sri Lestari, Aris; Evi, Margaretha (Jurnal Indonesia Sosial Sains, 2022)
In the modern era as it is currently developing a practical and instant lifestyle that affects almost all humans in the world. This certainly affects business competition which is then responded by most manufacturers in designing products that suit the needs of the instant lifestyle of the community. This explains that fast food restaurants have grown rapidly with the increasing need for customers to visit fast food restaurants. This study aims to focus on explaining the effect of the variable price (price), product quality (product quality) and promotion (promotion) on purchasing decisions. In this study, using a qualitative research approach and literature study or library research that is useful for obtaining a series of descriptions of the factors that influence the results of the variables studied. The results of this research explain that the better the perception of consumer prices, the more impact on purchasing decisions for a product or service. On the other hand, the quality of the product influences the purchasing decision the higher and the value resulting from the quality of the product made by the company, the higher the consumer's decision to purchase a product or service. And lastly, the quality of service affects the point of purchase decisions, the better the service provided, the more impact on purchasing decisions.